Do Various Sectors Respond to Oil Price Shocks? New Evidence for Indonesia as Emerging Market - Sukarno, Subiakto; Setiawati, Marla (International Journal of Energy Economics and Policy, 2020)
Oil is one of the world’s most widely used factor inputs in the manufacture of goods and services. Generally speaking, we believe that oil-dependent sectors will be more sensitive to shocks in oil prices. This paper aims to evaluate the response of different sectors as an emerging market to oil price shocks in Indonesia. The monthly data is used from January 2000 to February 2019. This study uses the Vector Auto-Regressive (VAR) model and the Impulse Reaction Function looks in-depth. The results show that shocks in oil prices can be significantly negative or positive for Indonesia’s various sectors. First, we find that all Indonesia’s sector index has the significant impact of oil price shocks. Second, the positive impact comes from the mining sector, while the remaining industries have a negative impact due to shocks in oil prices. The practical implications of this research are very useful not only to see the impact of Indonesia’s role as an emerging market and net oil importer which is for the investor in the mining area but also to others sector and regulators. Keywords: Oil prices shocks, Vector Auto-Regressive Model, Impulse Reaction Function JEL Classifications: Q4, M2 DOI: https://doi.org/10.32479/ijeep.9477